A conceptual framework for waste identification and reduction in Nigerian sandcrete blocks production process. Issue 3 (31st May 2019) - Aka, Adefemi; Bamgbade, Abosede Adebisi; Saidu, Ibrahim; Balogun, Oladimeji Moses
Abstract : Purpose: Non-value adding activities or waste have been a major challenge for the construction industry. Researchers worldwide have investigated how such activities can be reduced or overcome in the industry. However, much has not been done regarding waste in the production process of building blocks. Therefore, this study aims to investigate the various waste in sandcrete blocks production process (SBPP). The study also aims to find out the causes of the waste and their impacts on the factory performance. Design/methodology/approach: To achieve the aims of this study, a qualitative study was conducted in five sandcrete blocks firms in Minna. Physical observation and interviews were the main instruments used for data collection. The data obtained were analyzed through content analysis. Samples of blocks (low standard only) were also taken to the laboratory for compressive and porosity tests. Thereafter, questionnaires were administered to other sandcrete blocks producers in six firms. The essence of this was to investigate the applicability of the identified waste in other factories in the study context and for further data analysis. Findings: Typical forms of waste in SBPP are excessive stocking of sand and cement, long distance covered from the store to the mixing or production location, excessive quantity or over design of materials and over vibration or compaction of the newly produced blocks. It is anticipated that adoption of lean concepts, tools and techniques in the production of sandcrete blocks will help to eradicate the identified waste in the process and stimulate a future state value stream mapping (VSM). The practicality of the expected future state VSM is presently being investigated by one of the five firms in the study context. Research limitations/implications: The findings of the study mainly provide further insights on the various process waste in Nigerian sandcrete blocks production. Practical implications: The study provides knowledge on how lean thinking can be adopted to identify and reduce waste in SBPP. Such knowledge may be beneficial to the present and prospective sandcrete blocks producers. The study also provides insight on how the overall cost of production of sandcrete blocks and the quantity of CO2 that is being released into the atmosphere in the production process can be reduced. The VSM in the proposed framework also serves as a tool that can be globally adopted for waste identification by producers of other forms of blocks such as bricks. Originality/value: This paper satisfies all the tenets of originality as it has not been previously published and all the information obtained from other studies have been duly referenced. The study is also original as it is first in the study context to propose for a lean framework that can be used to reduce waste in SBPP.